已知y+2x=1,求代数式(y^2+2y+1)-(y^2-4x)的值
1个回答
(y^2+2y+1)-(y^2-4x)
=2y+4x+1
=2(y+2x)+1
=3
相关问题
已知y+2x=1,求代数式(y+1)^2-(y^2-4x)的值,
已知y+2x=1,求代数式(y+1)2-(y2-4x)的值.
已知2x+y=4,求代数式[(x+y)2-(x-y)2-2y(x-[1/2]y)]÷4y的值.
已知2x+y=4,求代数式[(x+y)2-(x-y)2-2y(x-[1/2]y)]÷4y的值.
已知Y+2X=1,求代数式(Y+1)^-(Y^-4X)的值.
已知1/x-1/2y=1/3求代数式2x+3y-4y/x-3y-2y的值
已知|x-1|+(y-1)^+0.求代数式(x^2+4xy-2y^2)-(x^2+y)-1/2(x-8y^2)的值!
求代数式的值已知x=1/3,y=1/4,求代数式x-(x+y)+(x+2y)+……(x+103y)的值
已知x-2y=1,xy=-2求代数式4x^2y^4-4^3y^3+x^4y^2的值
已知4x-3y=2,求代数式[(x^2 +2y)^2+4y(x-y)]/(-2y)的值